Developing student's nascent digital entrepreneurial model - Susetyo Darmanto; Adi Ekopriyono; Djoko Darmawan (Global Business & Finance Review (GBFR), 2022)
Purpose: The purpose of this study was to analyze the effect of entrepreneurial orientation on entrepreneurial competence, the effect of entrepreneurial competence, entrepreneurship knowledge, environmental support on entrepreneurial self-efficacy, and the influence of entrepreneurial competence, entrepreneurial self-efficacy, and environmental support on student's nascent digital entrepreneurs in Semarang, Indonesia. Design/methodology/approach: This study uses a quantitative approach with a survey to collect data.Research respondents are 143 students in Semarang who have digital businesses. The research analysis was carried out using PLS-SEM. Findings: The result showed that entrepreneurial orientation has a positive influence on entrepreneurial competence. Furthermore, entrepreneurial knowledge, entrepreneurial competence, and environmental support have a positive effect on entrepreneurial self-efficacy. The study proves environmental support and self-efficacy have a positive effect on digital entrepreneurial behaviors. However, entrepreneurial competence has no influence on digital entrepreneurial behaviors. Research limitations/implications: This study has several limitations: the object of analysis is one area in Semarang, and only five factors that influence digital entrepreneurial behavior. Future research should expand the scope of research to more areas, and add antecedents to the model so that the results can be generalized. Originality/value: The study is highlighting the important of developing nascent digital entrepreneurs of university students because they are the answer of the necessity of the 4th industry revolution.
Keywords: 650; entrepreneurial competence; entrepreneurial knowledge; environmental support; entrepreneurial self-efficacy; student's nascent digital entrepreneur